Prevalencia de Bruxismo en Estudiantes de odontología Sede Bucaramanga (2022)
Bruxism is a diurnal or nocturnal parafunctional activity derived from the combination of some occlusal disharmony with psychological factors, such as nervous tension or emotional overload, which leads to conscious or unconscious clenching or grinding of the teeth, involving a large number of problems for the system. stognatic Its prevalence during wakefulness is 22.1% to 31%.